Internalization Of Local Wisdom Values To Support The Policy Of Reducing Stunting In Tinukari Village, North Kolaka Regency - Umbarsari, Dewi (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
This study aims to understand and analyze the role of local wisdom values ​​in supporting stunting reduction policies in rural areas. The research location was in Tinukari Village, Wawo District, North Kolaka Regency. The urgency of this study stems from the phenomenon of stunting cases which are still a national problem, so that it requires serious handling from all levels of government, from the national level to the village government level. The seriousness of the village government in handling stunting must continue to be encouraged in order to welcome the demographic bonus in 2030 and the vision of a golden Indonesia in 2045. In this study, data collection was carried out through interviews and documentation studies. While data analysis was carried out with a three-flow process procedure, namely: data reduction, data presentation, and drawing conclusions. The results of the analysis show that the stunting handling policy carried out by the Tinukari village government is based on input from various elements of society at the stunting discussion event in the village. The stunting discussion activity is one of a series of pre-deliberations at the village level in order to prepare the Tinukari Village Government Work Plan (RKP) every year. The strategies carried out include: (1) encouraging the back to nature movement. This movement is carried out by maximizing the potential of agricultural products owned by Tinukari village. By encouraging residents, especially pregnant and breastfeeding mothers, to consume fresh vegetables from their own gardens; (2) building collaboration and synergy based on local wisdom. The concrete efforts made through this movement are to revive the spirit of "mepokoaso" (united/mutual cooperation) in solving every problem of community life according to their respective roles in society. Penelitian ini bertujuan memahami dan menganalisis peran nilai kearifan lokal dalam mendukung kebijakan penurunan stunting di pedesaan. Lokus penelitian dilakukan di Desa Tinukari Kecamatan Wawo Kabupaten Kolaka Utara. Urgensi dari penelitian ini berangkat dari fenomena kasus stunting yang masih menjadi masalah secara nasional, sehingga memerlukan penanganan yang serius dari semua level pemerintahan, dari tingkat nasional hingga di tingkat pemerintahan desa. Keseriusan pemerintah desa dalam penanganan stunting harus terus didorong dalam rangka menyongsong  bonus demografi tahun 2030 dan visi Indonesia emas tahun 2045. Dalam penelitian ini, pengumpulan data dilakukan melalui wawancara dan studi dokumentasi. Sedangkan analisis data dilakukan dengan prosedur tiga alur proses, yaitu: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil analisis menunjukkan bahwa strategi kebijakan penanganan stunting yang dilakukan oleh pemerintah desa  tinukari didasarkan hasil masukan dari berbagai elemen masyarakat pada acara kegiatan rembuk stunting di desa. Kegiatan rembuk stunting merupakan salah satu rangkaian pra musyawarah di tingkat desa dalam rangka penyusunan Rencana Kerja Pemerintah (RKP) Desa Tinukari setiap tahunnya. Adapun strategi yang dilakukan antara lain adalah: (1) menggalakkan gerakan kembali ke alam (back to nature). Gerakan ini dilakukan dengan memaksimalkan potensi hasil pertanian yang dimiliki oleh desa tinukari. Dengan mendorong warga masyarakat terutama kaum ibu hamil dan menyusui untuk mengkonsumsi sayur-sayuran segar dari hasil kebun sendiri; (2)  membangun kolaborasi dan sinergi dengan berbasis kearifan lokal. Upaya konkrit yang dilakukan melalui gerakan ini adalah membangkitkan kembali spirit “mepokoaso” (bersatu/bergotong royong) dalam menyelesaikan setiap persoalan kehidupan kemasyarakatan sesuai dengan peran masing-masing dalam masyarakat.